Assessing the contents of the psychological contracts: a cross-sectional survey of the academics at an Australian university - Krivokapic-Skoko, B.; O'Neill, Grant; Dowell, D. (ER Publishing Ltd, 2009)
This paper addresses the content of psychological contracts within academia and provides some empirical evidence from an Australian University. Using exploratory factor analysis of the data collected from the cross-sectional survey this research classified the academics’ obligations to the University as meeting academic expectations, commitment; and ‘above and beyond’. With regard to the University’sobligations as perceived by the academics the research identified the following eight underlying factors: fair treatment in promotion; staff development and support; good management and leadership; academic life; fairness and equity; appropriate remuneration; rewarding performance; and, good workplace relations. The initial cluster analysis allowed for some unpacking of the effects of such characteristics as gender, age, position level, union membership, and length of employment upon thecontent of the psychological contract. What emerged from the analysis is that each of these dimensions is an important factor with regard to psychological contract content and effects. It is critical for the University and the academics to be sensitive to possible differences in expectations, since unrealised expectations may result in demotivation, decreased commitment, increased turnover, and loss of trust in the organisation. These contracts motivate employees to fulfil commitments made toemployers when they are confident that employers will reciprocate and fulfil their side of the contracts.